Photon Quantization in Sm3+ Doped Red Glass Phosphors for Laser‐Induced Illumination. Issue 13 (18th May 2018) - Zhang, Yuhang; Li, Desheng; Zhao, Xin; Pun, Edwin Yue Bun; Lin, Hai
Abstract : Multi‐peak red fluorescence emissions in Sm 3+ ‐doped multicomponent‐alkali‐alkaline‐borate (MCAAB) glasses for laser‐induced illumination are quantitatively characterized, revealing that the quantum yield (QY) is closely related with the wavelength of pumping sources. Under the excitation of 370 nm UVA‐LED, the net emission photon numbers of 1.00 wt% Sm2 O3 ‐doped MCAAB glasses are derived to be 58.0 × 10 12 cps, and the QY reaches to 25.3% which is about twice as much as 12.2% under 469 nm blue‐LED pumping, which is attributed to the better excitability in UVA spectral region. In order to extend the effective excitation range to UVB, Ce 3+ is co‐doped in Sm 3+ ‐doped MCAAB glasses as a sensitizer, which results in an enhancement of Sm 3+ excitation intensity by a maximum sensitization factor of 9.16 in the UVB region. Absolute spectral parameters under 453 nm blue laser excitation exhibit that net emission photon numbers are up to 199.4 × 10 12 cps in 1.00 wt% Sm2 O3 doping case, and QY is solved to be 6.2%. Higher QY of the Sm 3+ ‐doped MCAAB glasses is expected to be achieved by further adopting wavelength‐matched pumping laser, implying that Sm 3+ ‐doped MCAAB glasses is a promising candidate as high power‐density light source in special laser‐induced illumination. Abstract : Sm 3+ ‐doped MCAAB glasses are investigated as laser‐driven illumination materials. Their effective excitation range is extended to UVB by co‐doping of Ce 3+ . Laser‐induced radiation behaviors are exhibited by absolute spectral characterization. Quantum‐yield dependence on excitability of pumping wavelength is identified. Efficient red fluorescence for special lighting is expected under matched laser pumping.